Vulnerability in Margaret Atwood’s “Rape Fantasies”: A Game of Cards About Life - Workman, Nancy (Studies in Canadian Literature, 2000)
Since there have been no thorough and sustained readings of Margaret Atwood’s popular short story "Rape Fantasies," its serious comments on sexual assault have been ignored in favour of concentrations upon its humour and its irony. Two important aspects are the bridge game, which serves to express notions of manipulation and control, mastery and vulnerability, and Sondra’s telling silence in the face of the narrator’s evident failure to fully understand what the effects of rape are. In turn, Estelle unknowingly implies her own vulnerability to possible sexual assault, because of her credulity to popular myths surrounding the problem of rape.